2021
DOI: 10.1007/s12564-021-09669-x
|View full text |Cite
|
Sign up to set email alerts
|

Who achieves superior rates of upward social mobility and better labor market outcomes in China: international student returnees or postgraduates who study domestically?

Abstract: Given the growth in student mobility and transnational higher education, there is an abundance of research on international students’ studying and living experiences in a new environment. However, their poststudy transitions and social mobility have rarely been touched. This study addresses how student returnees perform in China’s labor market and social mobility, following their accomplishment of their master degree in the UK and return to China. In theoretical considerations of the graduates’ social mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 58 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…This thesis will concentrate on the inequalities in the employability of Chinese students who obtain Master's Degree in UK universities and those who obtain Master's Degree in local Chinese universities. As revealed in Zhai and Gao (2021), and Xiong and Mok (2020) are research, UK returnees seem more employable than their peers with same-level degrees in Chinese universities in the labour market of large cities in China, this thesis will use cultural capital and human capital respectively to explain this phenomenon. The first section of this essay begins with a brief presentation of this educational inequity issue concerning the same degree leading to different employability.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…This thesis will concentrate on the inequalities in the employability of Chinese students who obtain Master's Degree in UK universities and those who obtain Master's Degree in local Chinese universities. As revealed in Zhai and Gao (2021), and Xiong and Mok (2020) are research, UK returnees seem more employable than their peers with same-level degrees in Chinese universities in the labour market of large cities in China, this thesis will use cultural capital and human capital respectively to explain this phenomenon. The first section of this essay begins with a brief presentation of this educational inequity issue concerning the same degree leading to different employability.…”
Section: Introductionmentioning
confidence: 87%
“…For students with a Bachelor's degree in China, if they desire to pursue a Master's degree, it can be classified into international degrees and Chinese degrees (Zhai & Gao, 2021). Firstly, Chinese undergraduate students who choose to enter overseas institutions for further study.…”
Section: Uk Master Degree Returnees Verse Chinese Domestic Postgraduatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, studying abroad facilitates students' expectations and practices regarding future career development and upward social mobility (Ma, 2020;Tsang, 2013;Zhai & Gao, 2021). For Chinese students and their parents, the desire for American college education is rooted in an urgent social mobility quest (Ma, 2020).…”
Section: Overview Of Chinese Students Studying Abroadmentioning
confidence: 99%
“…For Chinese students and their parents, the desire for American college education is rooted in an urgent social mobility quest (Ma, 2020). Surveys have also shown that studying abroad especially qualifications from elite overseas universities positively improves Chinese students' job-seeking outcomes, starting salaries, and career development (Hao & Welch, 2012;Hao et al, 2016;Mok et al, 2016;Zhai & Gao, 2021). Hence, to secure a generational reproduction of class status and mobility for offspring, middle-class parents deliberately capitalize on privileged social capital and send their children to study abroad, especially if they have failed to gain entrance to premier Chinese universities.…”
Section: Overview Of Chinese Students Studying Abroadmentioning
confidence: 99%